The Biomechanical Effects of Limited Lateral Retinacular and Capsular Release on Lateral Patellar Translation at Various Flexion Angles in Cadaveric Specimens - Jourdan M. Cancienne, M.D; David R. Christian, M.D; Michael L. Redondo, M.D; Hailey P. Huddleston, B.S; Elizbeth F. Shewman, M.S; Jack Farr, M.D; Brian J. Cole, M.D., M.B.A; Adam B. Yanke, M.D., Ph.D (Elsevier, 2019)
Purpose: To determine the biomechanical effect of limited lateral retinacular and capsular release on lateral patellar translation as a function of constant force at various knee flexion angles. Methods: Six pairs of bilateral cadaveric knee specimens (12 knees) were obtained from a tissue bank, dissected, and potted in a perfect lateral position based on fluoroscopy. A direct lateral force was applied to the patella through an eye screw in the midpoint of the lateral patella, and each knee underwent testing in the intact state and after lateral retinacular and capsular release. All knees were tested at 0°, 10°, 20°, 30°, 45°, 60°, and 90° of flexion using a custom-machined jig on a materials testing system with a 20-N lateral force applied to the patella. Patellar displacement was recorded and compared for each specimen. Results: Lateral displacement was significantly greater at all degrees of flexion for the lateral-release specimens than for an intact lateral retinaculum (P < .05). Compared with intact specimens, lateral-release specimens experienced 30% more translation at 0° of flexion and between 6% and 9% more lateral translation at 10° to 90° of flexion. Conclusions: Lateral retinacular and capsular release results in significantly increased lateral patellar translation at all flexion angles compared with intact specimens. This finding suggests that the lateral retinaculum may function as a significant restraint to lateral translation even with intact medial soft-tissue restraints. Clinical Relevance: Arthroscopic and open limited lateral retinacular releases should be performed with extreme caution when treating lateral patellar instability given the lateral retinaculum's apparent role as a secondary restraint.